Contractive conditions in b-metric spaces - Došenović, Tatjana M.; Pavlović, Mirjana V.; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The purpose of this paper is to consider various contractive conditions in b-metric spaces which have been recently published. Our results improve and complement many recent results from this field. Using the recently obtained result by R. Miculescu and A. Mihail (Miculescu & Michail, 2017, pp.1-11) the authors of this article show that the proofs of the majority of known results in the context of b-metric spaces can be shortened.
Keywords: metric space; common fixed point; altering distance function; point of coincidence; weak compatibility